The Validity Justice: Immanuel Kant’s Perspective in Court Decisions on Judicial Corruption (The Case of Sudrajad Dimyati) - Pamungkas, Ery; Surono, Agus; Nur Hidayati, Maslihati (Journal Research of Social Science, Economics, and Management, 2025)
Judicial corruption within the Indonesian judiciary represents a profound moral crisis that undermines public trust in legal institutions. This study examines the Bandung District Court Decision Number 23/Pid.Sus-TPK/2023/PN.Bdg against Sudrajad Dimyati, a Supreme Court justice convicted of bribery, through the lens of Immanuel Kant’s moral philosophy. Rather than employing conventional legal-formal analysis, this research adopts a deontological ethical approach to evaluate whether the court’s verdict fulfilled substantive justice principles. The research investigates two primary questions: (1) Whether the judicial decision satisfies Kantian principles of justice regarding universality, respect for dignity, moral autonomy, and procedural fairness; and (2) How Kant’s moral philosophy can inform the development of judicial professional ethics codes in Indonesian courts. This qualitative investigation employs document analysis and philosophical content analysis of the case decision and relevant moral philosophy literature. Findings demonstrate that while the verdict adhered to formal positive law requirements, significant tensions emerged regarding consistency of legal precedent when the appellate court reduced sentences based on humanitarian grounds. Most critically, the institutional system has not yet internalized moral autonomy and universal ethical principles as foundational to judicial governance. This research concludes that implementing four Kantian principles—universality, respect for dignity, moral autonomy, and procedural justice—establishes essential foundations for deontological ethics-based institutional reform of the Indonesian judicial system.